Leucine-rich alpha-2 glycoprotein as a potential biomarker for large vessel vasculitides - Umezawa, Natsuka; Mizoguchi, Fumitaka; Maejima, Yasuhiro; Kimura, Naoki; Hasegawa, Hisanori; Hosoya, Tadashi; Fujimoto, Minoru; Kohsaka, Hitoshi; Naka, Tetsuji; Yasuda, Shinsuke (Frontiers in Medicine, 2023)
Objectives Serum levels of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) have been used as useful biomarkers for reflecting the activity of large vessel vasculitides (LVV). However, a novel biomarker that could have a complementary role to these markers is still required. In this retrospective observational study, we investigated whether leucine-rich α-2 glycoprotein (LRG), a known biomarker in several inflammatory diseases, could be a novel biomarker for LVVs. Methods 49 eligible patients with Takayasu arteritis (TAK) or giant cell arteritis (GCA) whose serum was preserved in our laboratory were enrolled. The concentrations of LRG were measured with an enzyme-linked immunosorbent assay. The clinical course was reviewed retrospectively from their medical records. The disease activity was determined according to the current consensus definition. Results The serum LRG levels were higher in patients with active disease than those in remission, and decreased after the treatments. While LRG levels were positively correlated with both CRP and erythrocyte sedimentation rate, LRG exhibited inferior performance as an indicator of disease activity compared to CRP and ESR. Of 35 CRP-negative patients, 11 had positive LRG. Among the 11 patients, two had active disease. Conclusion This preliminary study indicated that LRG could be a novel biomarker for LVV. Further large studies should be required to promise the significance of LRG in LVV.